Impact of higher education, research, institutional quality, and information and communication technology on carbon emissions: Evidence from West Africa - Elom, Chinyere Ori; Nejad, Jalil Ghassemi; Ayerakwa, Hayford Mensah; Uwaleke, Chidebe Chijioke; Onyeneke, Robert Ugochukwu (International Journal of Innovative Research and Scientific Studies, 2025)
The study analyzes the impact of institutional quality, information and communication technology (ICT), higher education enrollment, and research on carbon emissions and intensity in West Africa. The study used panel data from 12 West African countries, covering the 2009-2020 period, which were obtained from the World Development Indicators database. We applied econometric methods such as fixed and random effects and the generalized method of moments for data analysis. Our findings indicate that while higher education increased carbon intensity, research (proxied as the number of scientific publications) increased carbon emissions in the region. However, both ICT and institutional quality significantly decreased carbon emissions and intensity in West Africa. That is, as the quality of institutions and governance in West Africa improves and ICT usage increases, carbon intensity and emissions decrease, invariably supporting the carbon neutrality objectives of West African governments. The findings will help to shape policy discussions on how to integrate economic development and climate goals, as well as provide insights for regional and global sustainability efforts.